(untitled) (Docentes 2.0 Journal, 2025)
Currently, basic education has important challenges that must be addressed. The student’s active participation in the construction of knowledge must be encouraged using current methodologies. The objective of the research was to carry out a systematic review of bibliographic information in the databases Science Direct, Scopus, Web of Science, and Embase from 2020 to 2024 on PBL and CT in EP, where studies have been carried out that report that PBL is related to CT; The research was based on the systematic method, humanistic paradigm, quantitative approach, with a narrative design, exploratory documentary type, and longitudinal section. Eight hundred thirty-five records were identified in the databases: Science Direct (406), Embase (187), Scopus (150), and Web of Science (92). After applying the inclusion and exclusion criteria, the final sample consisted of 7 articles. The recommendations made in the Prisma Declaration were followed. Among the results obtained, active learning, such as PBL, is fundamental in the development and training of the student and in strengthening the CT. About the discussion of the results, the application of PBL in EP demonstrates a significant influence on the development of CT. PBL has been revealed as an effective methodology for promoting interpretation, analysis, evaluation, and inference skills. About the conclusions, we can establish that PBL can potentially transform educational practice by promoting advanced cognitive skills.